2013
DOI: 10.1111/acps.12234
|View full text |Cite
|
Sign up to set email alerts
|

Regional cortical thinning may be a biological marker for borderline personality disorder

Abstract: The pattern of regions exhibiting cortical thinning in patients resembles a network of cortical structures repeatedly shown to be involved in social cognition. The results of the DDF analyses suggest that the thinning may partly be related to interpersonal dysfunction in patients with BPD. The pattern of thinning may represent a potential biological marker for BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 82 publications
3
13
0
Order By: Relevance
“…Further studies with multimodel (e.g., task‐related) are needed to clarify the relationship between asymmetry (more right lateralization) of ACC&AI and attention impulsiveness in patients with BPD. Besides, the asymmetry in this study was similar to the findings in a previous study that both left frontolimbic cortex (such as temporal pole and lateral orbitofrontal cortex) and frontal pole were reduced more than the right in BPD patients , which might suggest that the left‐right asymmetry could exist in other frontolimbic regions but not just in ACC&AI.…”
Section: Discussionsupporting
confidence: 90%
“…Further studies with multimodel (e.g., task‐related) are needed to clarify the relationship between asymmetry (more right lateralization) of ACC&AI and attention impulsiveness in patients with BPD. Besides, the asymmetry in this study was similar to the findings in a previous study that both left frontolimbic cortex (such as temporal pole and lateral orbitofrontal cortex) and frontal pole were reduced more than the right in BPD patients , which might suggest that the left‐right asymmetry could exist in other frontolimbic regions but not just in ACC&AI.…”
Section: Discussionsupporting
confidence: 90%
“…This method does not compare groups for thickness but rather identifies patterns of higher and lower thickness within a group and then tests whether patterns can identify group membership. Such patterns of altered cortical thickness would help identify potential imbalances between brain regions, as well as make inference on behavior that is related to the identified regions (Boen et al, ; Metzler‐Baddeley, Caeyenberghs, Foley, & Jones, ). Based on our previous observation of increased volume in orbitofrontal and insular cortex in this data set, we predicted that orbitofrontal and insular regions would be relatively higher compared to other regional thickness measures in the AN groups and predict membership in the AN or REC‐AN group.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Freesurfer analysis of cortical morphology, being automated, could have a series of limitations such as errors regarding processes of segmentation, normalization and skull extraction [15]. Another study on female BPD using Freesurfer package showed reduced cortical thickness in prefrontal cortex, left tempoparietal junction, bilateral temporal poles and bilateral paracentral lobules [7]. The authors conclude that the regions that exhibit cortical thinning in BPD patients resembles a network of cortical structures involved in social cognition [7].…”
Section: Introductionmentioning
confidence: 99%